الخداع التسويقي والصورة الذهنية لدى الزبون الجزائري :اتصالات الجزائر فرع سوق أهراس دراسة ميدانية - رندة بوشرمة; نادية رواينية (My University, 2021)
The main objective of this study is to know the effect of marketing deception on the mental image of the Algerian customer as the most important elements of interest to the organization, when the phenomenon of marketing deception spread, it made many believe that the success of institutions is linked to marketing deception practices in all regions. The hypotheses of the study were selected on a sample of 30 Algeria telecom customers in the state of souk Ahras, using the regression coefficient through the use of a program (SPSS), the results of the study indicated that the most of the marketing deception practices have a medium and statistically significant effect on the mental image of the Algerian customer, except for the deception practiced in the distribution, it has no effect on the mental image. As for the main hypothesis, a strong and statistically significant effect of marketing deception on the mental image was founa. .............................................................. لهدف الأساسي من هذه الدراسة هو معرفة تأثير الخداع التسويقي على الصورة الذهنية للزبون الجزائري باعتباره من أهم العناصر التي تهم المنظمة، فعندما انتشرت ظاهرة الخداع التسويقي جعلت الكثيرين يعتقدون أن نجاح المؤسسات يرتبط بممارسات الخداع التسويقي في جميع المناطق. تم اختيار فرضيات الدراسة على عينة مكونة من 30 من عملاء اتصالات الجزائر بولاية سوق أهراس، وذلك باستخدام معامل الانحدار من خلال استخدام برنامج (SPSS)، أشارت نتائج الدراسة إلى أن معظم ممارسات الخداع التسويقي لها تأثير متوسط ​​وذو دلالة إحصائية على الصورة الذهنية للزبون الجزائري، باستثناء الخداع الذي يمارس فيه التوزيع ليس له أي تأثير على الصورة الذهنية. أما الفرضية الرئيسية فهي وجود تأثير قوي وذو دلالة إحصائية للخداع التسويقي على الحالة النفسية